The enemy at home : the cultural left and its responsibility for 9/11 - D'Souza, Dinesh, 1961- (Doubleday, 2007)
The culture wars at home and the global war on terror are usually viewed as separate problems. Author D'Souza makes the claim that terrorist acts around the world can be directly traced to the ideas and attitudes perpetrated by America's cultural left. D'Souza shows that American liberals are responsible for fostering a culture that angers and repulses not just Muslims but also traditional and religious societies around the world. He argues that it is not our exercise of freedom that enrages our enemies, but our abuse of that freedom--from the sexual liberty of women to the support of gay marriage, birth control, and no-fault divorce, to the aggressive exportation of our vulgar, licentious popular culture. It is only by curtailing the left's attacks on religion, family, and traditional values that we can persuade moderate Muslims and others around the world to cooperate with us and shun the extremists in their own countries.--From publisher description.